Determinants of neuronal firing patterns in the hippocampus - Tukker, JJ (2009)
The activity of networks subserving memory and learning in the hippocampus is under the control of GABAergic interneurons. In order to test the contribution of distinct cell types, I have recorded extracellularly, labelled, and identified different types of interneuron in area CA3 of the hippocampus, a region implicated in the generation of gamma and theta oscillations, and the initiation of sharp-waves. I present here a detailed analysis of the spike timing of parvalbumin-positive (PV) basket and physiologically identified pyramidal cells in area CA3, relative to various network states recorded in area CA3 and CA1 simultaneously. Additionally, I have shown by detailed analysis that five classes of previously recorded and identified CA1 interneuron fired with cell type specific firing patterns relative to local gamma oscillations. In CA3, PV basket cells fired phase locked to theta and gamma oscillations recorded in CA1 as well as in CA3, and increased their firing rates during CA1 sharp-waves. Pyramidal cells in CA3 were also phase-locked, but fired at phases different from basket cells. During theta oscillations, CA3 pyramidal and PV basket cells were phase locked to both CA1 and CA3 theta equally, suggesting a wide coherence of these oscillations; in contrast, cells fired more strongly phase-locked to gamma oscillations in CA3 than in CA1, suggesting a specific role for CA3 in the generation of this rhythm. In contrast to theta and gamma oscillations, CA3 basket cells were phase-locked to ripples in area CA3 but not in CA1. Overall, my results show that the spike timing of several types of interneuron in CA1, and PV basket cells in CA3, is correlated in a cell- and area-specific manner with the generation of particular states of synchronous activity.